Hak Paten Merek Sebagai Perlindungan Hukum dan Keberlanjutan Bisnis UMKM Kopi Lelet Cangkir dalam Bersaing - Hersugondo Hersugondo; Sugeng Wahyudi; Ahyar Yuniawan; Idris Idris (Universitas Muhammadiyah Semarang, 2022)
Coffee is a popular Indonesian farmer's plant, coffee products have become a drink that is much favored by all levels of society and has even become a source of foreign exchange earnings from coffee exports. The demand for good coffee for local consumption and even imports continues to increase, the proliferation of shops that provide coffee drinks is increasingly driving the increase in demand for coffee products so that it is necessary to continue to be encouraged by MSMEs that are able to provide coffee products to meet the increasing demand. People's habits and hobbies of consuming coffee encourage a lot of coffee processing businesses to appear. One of the interesting things in Rembang Regency is the habit of consuming slow coffee. Lelet Coffee. et cup Rembang Regency is one of the coffee business actors that has good business development potential. The results of the survey and observations were continued by providing managerial and entrepreneurship training as well as assistance and various facilitation. The PKM team sees that the large business value in Kopi Lelet Cangkir needs to be protected with legal protection, especially brand rights. By having a patent for the Kopi Lelet cup brand, you will be more confident in your business competition so that you will be able to have a competitive advantage and long-term business sustainability.